Analisis Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Pengadilan Agama Kabanjahe Kelas II - Angkat, Fauji Armansah; Istiqamah, Nuraini Kemalasari; Pratama, Siswa (Universitas Negeri Medan, 2025)
This research is motivated by looking at the many phenomena that show workload and workenvironment have an important role in improving employee performance. The aim of this research is to describethe workload, work environment, and performance of employees at the Kabanjahe Religious Court. Thisresearch used a descriptive-qualitative approach with a sample size of 20 employees who were used asrespondents. The data source used in this research is primary data, with data collection techniques usingquestionnaire, observation and interview methods. The results of this research show that the workload at theKabanjahe Religious Court can be said to be still not appropriate because there is still excess work due to a lackof staff. Apart from that, the work environment is good; however, it still requires improvement in several areas,especially the completeness and suitability of facilities supporting work implementation. This has an impact onemployee performance because it can slow down the process of completing work. The performance of theemployees is also good; it's just that two-way communication is needed between leaders and employees toobtain in-depth information about employee performance problems